Micronutrient optimization for tissue engineered articular cartilage production of type II collagen - Cruz, Maria A.; Gonzalez, Yamilet; Vélez Toro, Javier A.; Karimzadeh, Makan; Rubbo, Anthony; Morris, Lauren; Medam, Ramapaada; Splawn, Taylor; Archer, Marilyn; Fernandes, Russell J.; Dennis, James E.; Kean, Thomas J. (Frontiers in Bioengineering and Biotechnology, 2023)
Tissue Engineering of cartilage has been hampered by the inability of engineered tissue to express native levels of type II collagen in vitro. Inadequate levels of type II collagen are, in part, due to a failure to recapitulate the physiological environment in culture. In this study, we engineered primary rabbit chondrocytes to express a secreted reporter, Gaussia Luciferase, driven by the type II collagen promoter, and applied a Design of Experiments approach to assess chondrogenic differentiation in micronutrient-supplemented medium. Using a Response Surface Model, 240 combinations of micronutrients absent in standard chondrogenic differentiation medium, were screened and assessed for type II collagen promoter-driven Gaussia luciferase expression. While the target of this study was to establish a combination of all micronutrients, alpha-linolenic acid, copper, cobalt, chromium, manganese, molybdenum, vitamins A, E, D and B7 were all found to have a significant effect on type II collagen promoter activity. Five conditions containing all micronutrients predicted to produce the greatest luciferase expression were selected for further study. Validation of these conditions in 3D aggregates identified an optimal condition for type II collagen promoter activity. Engineered cartilage grown in this condition, showed a 170% increase in type II collagen expression (Day 22 Luminescence) and in Young’s tensile modulus compared to engineered cartilage in basal media alone.Collagen cross-linking analysis confirmed formation of type II-type II collagen and type II-type IX collagen cross-linked heteropolymeric fibrils, characteristic of mature native cartilage. Combining a Design of Experiments approach and secreted reporter cells in 3D aggregate culture enabled a high-throughput platform that can be used to identify more optimal physiological culture parameters for chondrogenesis.